Quantum Sensing of Noisy and Complex Systems under Dynamical Control - Kurizki, Gershon (2016)
We review our unified optimized approach to the dynamical control of quantum-probe interactions with noisy and complex systems viewed as thermal baths. We show that this control, in conjunction with tools of quantum estimation theory, may be used for inferring the spectral and spatial characteristics of such baths with high precision. This approach constitutes a new avenue in quantum sensing, dubbed quantum noise spectroscopy.